PENGARUH KUALITAS LAYANAN, WORD OF MOUTH, DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS : INSTITUT BISNIS DAN TEKNOLOGI INDONESIA) - Wiyata Putra, I Dewa Putu Gede; Willdahlia, Ayu Gede; Dona Wahyu Aristana, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This study aims to examine the influence of digital marketing, word of mouth, and service quality on purchasing decisions at the Indonesian Business and Technology Institute (INSTIKI) as an effort to increase student enrollment amid the Covid-19 pandemic. The study was conducted using multiple linear regression methods involving 100 first-semester student respondents. The results of the study indicate that digital marketing, word of mouth, and service quality have a significant positive effect on purchasing decisions. The R² value shows that the influence of these three variables can only explain about 44.8 percent of the variation in purchasing decisions, while 55.2 percent are attributed to other factors. The results of this study are expected to assist the marketing team at INSTIKI in determining strategies to increase new student enrollment